Implementasi Sistem Penggerak Servo SG 90 Berbasis Arduino Uno dengan Kontrol Sudut Dinamis - Rayhan Al Hayubi; Salsabila Aulia; Dafairro Abbil Gunawan; Syarif Hidayatullah; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In this study, the implementation and simulation of a servo SG90 drive system based on Arduino Uno with dynamic angle control were carried out. The SG90 servo motor is widely used in various applications such as robotics and automation due to its ease of control and small size. The objective of this research is to develop a control system capable of adjusting the servo angle dynamically using Arduino Uno. The simulation method involves hardware and software simulations combined with servo control code based on PWM (Pulse Width Modulation) signals. The results show that the system is capable of accurately controlling the servo angle through a potentiometer as a dynamic input, along with simulation visualization in a software environment.